Reduction of Chickpea Pod Borer (Helicoverpa armigera L.) Population by Application of Selected Insecticides and Bio Pesticides - Khanjan Das; Anoorag R. Tayde; Suman Mohanty; Pedamallu Saiteja (Cutting Edge Research in Biology Vol. 1, 2022)
Chickpea pod borer (Helicoverpa armigera L.) has reported to be the most dangerous and notorious pest infesting upon the chickpea plant and incurring heavy losses. Chickpea is one of the important crops grown all over Uttar Pradesh and the farmers in these regions are facing a major issue related to the infestation of chickpea pod borer. Keeping it in view, the present research was conducted at the Central Research Field of Department of Agricultural Entomology, Sam Higginbottom University of Agriculture Technology and Sciences, Prayagraj during the Rabi season of 2021-22. Metarhizium anisopliae, Beauveria bassiana, Karanj Oil, Neem Oil, Spinosad, Emamectin benzoate + Indoxacarb, and Indoxacarb were the therapies employed in the study. The results showed that Emamectin benzoate 5% SG + Indoxacarb 14.5% SC (73.57%) had the largest percent reduction in larval population and was the most effective at reducing the larval population. It is then followed by Spinosad 45% SC (65.03%), Indoxacarb 14.5% SC (59.02%), Beauveria bassiana (1x108 cfu) (54.87%), Metarhizium anisopliae (1x108 cfu) (50.92%), Neem Oil 2% (45.81%) and Karanj Oil 2% (37.53%). The incorporation of botanicals with that of the novel insecticides has proved to be a beneficial one and also boosting up the sustainable agricultural practices.